A Retention Study of Learning a Graphical Software Application - Feizi, Andisheh; Wong, Chui Yin (The international journal of interdisciplinary educational studies, 2014)
This paper examines the effect of user interface styles for a retention study on a graphical software application. An empirical study was performed to investigate retention of learning a graphical software application, namely Microsoft Expression Blend® 4. Initially, 32 subjects learned to perform a series of tasks using Microsoft Expression Blend® 4. Subsequently, they carried out a set of tasks to accomplish a goal. Tasks involved using both graphical user interface (GUI) and command line interface (CLI). Subject’s performances were evaluated in association with several attributes in GUI interface and CLI styles. Performance variables (effectiveness, duration, efficiency rate, numbers of error and numbers of help) were measured for tasks performed by all 32 participants for an initial session. Participants carried out the same tasks to accomplish the similar goal after a three-week time interval. Performance variables were measured for tasks performed by all participants for retention session as well. Comparing the data gathered from initial session with the data from retention session indicated that the task performed via CLI style indicated very poor scores (in terms of effectiveness, efficiency rate, numbers of error and numbers of help) as opposed to the tasks performed via GUI styles. Retention of tasks relating to GUI style showed less decay unless it was a task done from a menu item with unfamiliar labels. However, the total number of errors and helps was significantly higher in the retention test rather than the original test.